Transport of Amino Acids in Soy Sauce Desalination Process by Electrodialysis - Man Wang; Shaoping Kuang; Xitong Wang; Daihao Kang; Debin Mao; Guanlan Qian; Xiaodan Cai; Ming Tan; Fei Liu; Yang Zhang (Membranes, 2021)
Soy sauce is a common condiment that has a unique flavor, one that is derived from its rich amino acids and salts. It is known that excessive intake of high-sodium food will affect human health, causing a series of diseases such as hypertension and kidney disease. Therefore, removing sodium from the soy sauce and retaining the amino acids is desirable. In this study, electrodialysis (ED) was employed for the desalination of soy sauce using commercial ion exchange membranes (IEMs). The influence of the current density and initial pH on the desalination degree of the soy sauce was explored. Results showed that the optimal desalination condition for ED was reached at a current density of 5 mA/cm2 and pH of 5, with the desalination degree of 64% and the amino acid loss rate of 29.8%. Moreover, it was found that the loss rate of amino acids was related to the initial concentration and molecular structure. In addition, the amino acid adsorption by IEMs was explored. Results implied that the molecular weight and structure affect amino acid adsorption. This study illustrated that the ED process can successfully reduce the salt content of the soy sauce and retain most of the amino acids without compromising the original flavor.